Integration of Sim City in learning urban Geography - Samuel Balbin (Universidade Estadual de Alagoas, 2024)
With the ever-evolving landscape of education, integration of mobile games into classroom instruction has been remarkable. However, with the advancement of technology, newly developed mobile apps are needed to be evaluated before they can be fully utilized in the teaching-learning process. This study delved into the integration of Sim City, a simulation game focused on constructing cities, into Urban Geography classes with primary focus on evaluating the mobile app's appropriateness, efficiency, and relevance, as well as its perceived impacts on motivation and metacognition of the users. The research involved the utilization of mixed-method approach using the explanatory sequential design where the survey method was utilized to determine the evaluation of the respondents on the given criteria and the interview to identify the difficulties and challenges encountered by the users which are the second-year BSE-Social Studies students. The quantitative data were analyzed using the mean by employing the Likert Scale and appropriate adjectival interpretations where it was revealed that the mobile app's integration was highly favored. The visual clarity and compatibility of Sim City with the course content had a good impact on its appropriateness. The efficiency results emphasized the game's capacity to improve understanding through a structured learning process and challenging tasks. The relevance was confirmed, particularly in advancing the ideas about smart cities. Furthermore, participants exhibited enhanced motivation and improved metacognitive abilities. Moreover, the qualitative data were coded and analyzed by employing the content-thematic analysis. It was found that challenges encountered by the respondents included game complexity, financial aspects and resource management, and technical issues.